An Expert System for Engine Excavator Troubleshooting - Ahmed, Bashar (Journal of Soft Computing and Data Mining, 2020)
Due to the rapid development in urban and rural area nowadays, the use of engine excavator is also increasing. However, currently there are no specific system to provide engine excavator diagnosis and troubleshooting. Engine excavator diagnosis and troubleshooting is only depending on human expert. Most existing systems only offer general information on excavator problems. Therefore, in this project, an expert system that aids users to do engine excavator troubleshooting with repair method recommendation solution was proposed. Engine excavator troubleshooting expert system enable users to do engine excavator troubleshooting via online. This expert system shall be used as a reference in engine excavator troubleshooting. Methodology used for this system develop-ment is Knowledge Engineering which consist of six important phases. The significance of this project is that user able to use the troubleshooting features and get the expert recommendation solution from this expert system.